Design and Development of a Low-Cost and Compact Real-Time Monitoring Tool for Battery Life Calculation - Dimitrios Rimpas; Vasilios A. Orfanos; Pavlos Chalkiadakis; Ioannis Christakis (Engineering Proceedings)
Lithium-ion batteries are utilized everywhere from electronic equipment, smartphones and laptops to electric vehicles; however, certain disadvantages are inherited including high-cost and low-temperature range, caused by high currents. In this paper, a compact and low-cost battery management system is presented which can measure the voltage and current for both the battery and power supply. Two NTC thermistors, 10k and 100K Ohm each, are exploited for collecting battery temperature in two different spots of the socket for direct comparison and validation while an additional sensor measures external temperature and humidity. A charging socket is provided for charging the cell through an external source with dynamic voltage output to test the battery response. Finally, an Arduino-compatible device is implemented in order to protect the battery from overcharging. This system collects parameters at a 10 s time rate and calculates precious parameters of the battery-like State of Charge (SoC), State of Health (SoH) and State of Power (SoP). Keeping the operation within a safe zone of 20–80% SoC maximizes longevity and ensures that it can provide even the maximum power to cover the load required; hence, these three parameters are considered collaborative. Afterwards, the collected data are sent over Wi-Fi on the internet application server for real-time monitoring, in an efficient, portable and low-cost setup.